Evidence for regional hippocampal damage in patients with schizophrenia. - Singh, Sadhana; Khushu, Subash; Kumar, Pawan; Goyal, Satnam; Bhatia, Triptish; Deshpande, Smita N (Neuroradiology, 2018)
Purpose: Schizophrenia patients show cognitive and mood impairments, including memory loss and depression, suggesting damage in the brain regions. The hippocampus is a brain structure that is significantly involved in memory and mood function and shows impairment in schizophrenia. In the present study, we examined the regional hippocampal changes in schizophrenia patients using voxel-based morphometry (VBM), Freesurfer, and proton magnetic resonance spectroscopy (H MRS) procedures. Methods: H MRS and high-resolution T1-weighted magnetic resonance imaging were collected in both healthy control subjects ( N = 28) and schizophrenia patients ( N = 28) using 3-Tesla whole body MRI system. Regional hippocampal volume was analyzed using VBM and Freesufer procedures. The relative ratios of the neurometabolites were calculated using linear combination model (LCModel). Results: Compared to controls, schizophrenia patients showed significantly decreased gray matter volume in the hippocampus. Schizophrenia patients also showed significantly reduced glutamate (Glu) and myo-inositol (mI) ratios in the hippocampus. Additionally, significant positive correlation between gray matter volume and Glu/tCr was also observed in the hippocampus in schizophrenia. Conclusion: Our findings provide an evidence for a possible association between structural deficits and metabolic alterations in schizophrenia patients.